A new highly efficient method for the preparation of phenyl-containing siloxanes by condensation of phenylsilanols in liquid ammonia. (16th January 2022) - Ershova, Tatyana; Anisimov, Anton; Krylov, Fedor; Polshchikova, Natalia; Temnikov, Maxim; Shchegolikhina, Olga; Muzafarov, Aziz
Abstract: A new simple and highly efficient method for the synthesis of phenylsiloxanes in a liquid inorganic medium, namely, ammonia at room temperature or 100 °C at elevated pressure, has been suggested. The method that requires no organic solvent in the reaction medium can be considered as a new "green" method for the preparation of organosiloxanes. The compounds were obtained in almost quantitative yields and were fully characterized by a set of physicochemical analysis methods: 1 H, 13 C, 29 Si NMR, IR-spectroscopy, HRMS ESI, GPC and elemental analysis.